Phonological similarity affects production of gestures, even in the absence of overt speech - Nozari, Nazbanou; Göksun, Tilbe; Thompson-Schill, Sharon L.; Chatterjee, Anjan (Frontiers in Psychology, 2015)
Are manual gestures affected by inner speech? This study tested the hypothesis that phonological form influences gesture by investigating whether phonological similarity between words that describe motion gestures creates interference for production of those gestures in the absence of overt speech. Participants learned to respond to a picture of a bottle by gesturing to open the bottle’s cap, and to a picture of long hair by gesturing to twirl the hair. In one condition, the gestures were introduced with phonologically-similar labels “twist” and “twirl” (similar condition), while in the other condition, they were introduced with phonologically-dissimilar labels “unscrew” and “twirl” (dissimilar condition). During the actual experiment, labels were not produced and participants only gestured by looking at pictures. In both conditions, participants also gestured to a control pair that was used as a baseline. Participants made significantly more errors on gestures in the similar than dissimilar condition after correction for baseline differences. This finding shows the influence of phonology on gesture production in the absence of overt speech and poses new constraints on the locus of the interaction between language and gesture systems.